Perbandingan Pengaruh Emotional Marketing dan Influencer Marketing terhadap Keputusan Pembelian melalui Daya Tarik Konsumen pada Nyfodd Kafe Citraland Surabaya - Kevin Widjojo; Hans Christian; Victor Kurniawan Yuwono (JURNAL ILMIAH EDUNOMIKA, 2026)
This study examines the effect of emotional marketing and influencer marketing on purchase decisions through consumer attraction at Nyfodd Kafe Citraland Surabaya. This study is motivated by the increasing role of digital marketing in the food and beverage industry, where visual content, emotional messages, and influencer recommendations can shape consumer attraction before purchase decisions occur. This employs a quantitative method and applies purposive sampling as the sampling technique. Data were collected from 120 respondents aged 18–35 years who had seen Nyfodd Kafe’s promotional content and had visited or purchased its products. The data were analyzed using SEM-PLS with SmartPLS software. The results show that emotional marketing and influencer marketing have a positive and significant effect on consumer attraction. Consumer attraction also has a positive and significant effect on purchase decisions. However, emotional marketing and influencer marketing do not have a direct effect on purchase decisions. Consumer attraction is proven to mediate the effect of both strategies on purchase decisions. Based on the comparison of path coefficient, F-square, and indirect effect values, emotional marketing is found to be more effective than influencer marketing in shaping consumer attraction and indirectly encouraging purchase decisions.